Assessment of the biopotency of follitropin alfa and lutropin alfa combined in one injection: a comparative trial in Sprague-Dawley rats - Ezcurra Diego; Dekkers Chris; Meyer Randal; Alper Michael; Schertz Joan; Kelly Eduardo (BMC, 2008)
Abstract Background The current study was designed to determine if follitropin alfa (recombinant human follicle-stimulating hormone; r-hFSH) and lutropin alfa (recombinant human luteinizing hormone; r-hLH) biopotencies were unchanged by reconstituting in sterile water for injection and mixing prior to injection. Methods The biopotencies of r-hFSH and r-hLH were determined following injection of female Sprague-Dawley rats with a mixture of follitropin alfa revised formulation female (RFF) and lutropin alfa (1:1, r-hFSH:r-hLH). Biopotencies of follitropin alfa RFF and lutropin alfa were measured using ovarian weight and ascorbic acid depletion assays, respectively, and compared with a reference standard. Stock mixtures of follitropin alfa RFF and lutropin alfa (1:1) were prepared within 1 h prior to each respective assay's injection and stored at 6 +/- 2°C. Separate low dose (follitropin alfa RFF 1.5 IU/rat, lutropin alfa 2 IU/rat) and high dose (follitropin alfa RFF 3 IU/rat, lutropin alfa 8 IU/rat) treatments were prepared from stock mixtures or individual solutions by diluting with 0.22% bovine serum albumin saline solution and injected within 1 h of preparation. The main outcome measures were ovarian weight and ovarian ascorbic acid depletion. Results FSH bioactivities were similar (p > 0.10) between the individual follitropin alfa RFF test solution (84.2 IU) and follitropin alfa RFF/lutropin alfa (87.6 IU) mixtures prepared within 1 h of injection and stored at 6 +/- 2°C. LH bioactivities were similar (p > 0.10) between lutropin alfa (94.7 IU) test solution and lutropin alfa/follitropin alfa RFF (85.3 IU) mixtures prepared within 1 h of injection and stored at 6 +/- 2°C for not more than 1 h prior to injection. Conclusion Mixing follitropin alfa RFF and lutropin alfa did not alter the bioactivity of either FSH or LH.